Didactic digital tools and autonomous learning in information technology engineering students at Uleam, Chone Extension - Mera-Santander, Nubia Aracely; Rivadeneira-Zambrano, Fabricio (International research journal of engineering, IT and scientific research, 2024)
The technological scenario has transformed the way people communicate, learn and carry out daily activities. Since the COVID-19 pandemic, it has been proven that technology has provided many advantages, but challenges related to access and security have also been generated, making it essential to guarantee that all people have the same opportunities related to scientific access. The objective was to evaluate the use of digital didactic tools in the autonomous learning of information technology engineering students of the ULEAM Chone extension, the study was descriptive with the quantitative approach, the inductive-deductive method was applied, the review of information and the statistical method. Among the instruments used in the work, a structured survey was used for the 16 teachers and information technology students with a total population of 193 students, applying the Larry and Murray formula with a sample of 89 schoolchildren. It is concluded that digital tools offer advantages in autonomous learning such as time optimization, in addition to allowing the analysis of various investigative approaches, even though there are factors that affect the educational field for the application of digital tools such as social, cultural, political and economic.